Sistem Indra: Penglihatan, Pendengaran, Pembau, Peraba, dan Perasa - Syilvana Agustina Dewi Wulandari; Vanesha Bilqis Nur Faiz; Virgiana Amanda Dwi Herlina; Wulan Dwi Utami; Yuna Julia Choirunisa; Liss Dyah Dewi Arini (INDO PUBLISHING, 2025)
The human sensory system plays a crucial role in daily life, receiving, processing, and responding to environmental stimuli. This study aims to describe the five primary sensory systems: sight, hearing, smell, touch, and taste, and to explain their relationship to surgical practice. The research method used was a literature review, analyzing various relevant, up-to-date scientific sources. The study results indicate that disorders of the sensory system can significantly impact a person's quality of life and health. Nurses play a crucial role in early detection, prevention, and health education related to maintaining sensory system function. Therefore, healthcare professionals need a comprehensive understanding of the sensory system to provide effective and comprehensive care.